Microwave and open vessel digestion methods for biochar. (January 2020) - Wathudura, Pathum D.; Peiris, Chathuri; Navarathna, Chanaka M.; Mlsna, Todd E.; Kaumal, M.N.; Vithanage, Meththika; Gunatilake, Sameera R.
Abstract: Digestion of biomass derived carbonaceous materials such as biochar (BC) can be challenging due to their high chemical recalcitrance and vast variations in composition. Reports on the development of specific sample digestion methods for such materials remain inadequate and thus require considerable attention. Nine different carbonaceous materials; slow-pyrolyzed tea-waste and king coconut BC produced at 300 °C, 500 °C and 700 °C, sludge waste BC produced at 700 °C, wet fast-pyrolyzed Douglas-Fir BC and steam activated coconut shell BC have been tested to evaluate a relatively fast and convenient open-vessel digestion method using seven digestion reagents including nitric acid (NA), fuming nitric acid (FNA), sulfuric acid (SA), NA/SA, FNA/SA, NA/H2 O2 and SA/H2 O2 mixtures. From the tested digestion reagents, SA/H2 O2 mixture dissolved low temperature produced BC (LTBC) within 2 h with occasional shaking and no external heating. Except peroxide mixtures, the other reagents were used to evaluate microwave digestion (MWD) efficiency. Nitric acid mixture was capable of only completely digesting LTBC in the MWD procedure whereas FNA, NA/SA and FNA/SA mixtures resulted in the successful dissolution of all tested carbonaceous materials. Amongst them, FNA provided the least matrix effect in the quantification of the four metals tested using flame atomic absorption spectrophotometry. Tested recoveries for FNA were satisfactory as well. It was concluded that FNA is a preferable reagent for microwave digestion of BC. Graphical abstract: Image 1 Highlights: Seven digestion reagents were tested to digest nine different biochars. H2 SO4 /H2 O2 mixture was best suited for open vessel digestion of biochar. Microwave digestion with fuming nitric acid digested all tested biochar types. Low matrix effects and acceptable recoveries were obtained by fuming nitric acid.